ĐÁNH GIÁ ĐỘC TÍNH BÁN TRƯỜNG DIỄN CỦA CHẾ PHẨM TỪ TẰM DÂU VÀ NẤM BẠCH CƯƠNG - Phạm, Khắc Linh; Ngô, Thanh Nam; Trần, Thanh Tuấn (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EVALUATION OF THE SUBCHRONIC TOXICITY OF PRODUCT PREPARED FROM BOMBYX MORI AND BEAUVERIA BASSIANAThe product prepared from bombyx mori and beauveria bassiana with the microbial fermentation technology is effective in health enhancement and treatment support of prostatic hypertrophy, gastritis, ulcerative colitis, etc. In this study, the subchronic toxicity of this product have been evaluated on experimental rabbit. The results show that, the product don’t affect the normal weight increment of rabbit and don’t change the indices of haematology, biochemistry, and anapathology between control group and test group